2011
DOI: 10.1007/s11743-011-1292-1
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Stability of Quaternary Ammonium Methyl Carbonates

Abstract: Quaternary ammonium compounds are used commercially for a variety of applications and some are of interest as ionic liquids. For many years dimethyl carbonate has been touted as a green reagent, including its use for methylation (quaternization) of tertiary amines. In addition, substitution of the methyl carbonate by other anions can be efficiently and cleanly accomplished by reaction with the corresponding acid. How stable are these methyl carbonate quaternary compounds? High field 13 C NMR shows that in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…However, in the process of alkali washing, if the concentration of NaOH is too high, TOMAC may be transformed into R 4 NOH, with poor stability. If the concentration of NaOH is too low, the number of alkali washings may need to increase, which affects the transformation efficiency (Weisshaar et al, 2012 ). Therefore, the effects of NaOH concentration and the number of alkali washings on the further conversion of -type quaternary ammonium salt and the extraction rate of As III were investigated, respectively, and the experimental results are shown in Figure 4 .…”
Section: Resultsmentioning
confidence: 99%
“…However, in the process of alkali washing, if the concentration of NaOH is too high, TOMAC may be transformed into R 4 NOH, with poor stability. If the concentration of NaOH is too low, the number of alkali washings may need to increase, which affects the transformation efficiency (Weisshaar et al, 2012 ). Therefore, the effects of NaOH concentration and the number of alkali washings on the further conversion of -type quaternary ammonium salt and the extraction rate of As III were investigated, respectively, and the experimental results are shown in Figure 4 .…”
Section: Resultsmentioning
confidence: 99%
“…Besides the methyl acetate formation, there are several side products formed. Tetrabutylammonium acetate can react with DMC and participate in Hoffman elimination reactions Figure shows the GC–MS of the compounds formed during the different experiments at 100 °C.…”
Section: Resultsmentioning
confidence: 99%
“…The stability of the methylcarbonate anion determines if hydrolysis (Figure , R.5) or a second methylation reaction (R.4) will occur. Alkylammonium methylcarbonate salts are stable at temperatures below 170–180 °C, but they hydrolyze promptly in the presence of water (R.5). An option for avoiding this hydrolysis step is to have an excess of methanol to push the equilibrium in the direction of the methylcarbonate anion. , …”
Section: Introductionmentioning
confidence: 99%
“…The Hofmann elimination has been well known since 1958 and is considered to be the main reaction pathway. 19,20 With hydroxide present, different elimination and substitution mechanisms are possible. 21 The Hofmann elimination proceeds via a nucleophilic attack of the anion on the 𝛽-hydrogen, relative to the nitrogen atom.…”
Section: Degradation Mechanismsmentioning
confidence: 99%
“…Other studies have shown that methyl carbonate can react with water to form methanol and bicarbonate. 20,30 This change in anion could result in a more stable QAS, which would explain the profound stabilizing effect that water facilitates.…”
Section: Degradation Kineticsmentioning
confidence: 99%